Ethnography of Communication in Improving Social Interaction of Children with Special Needs : Etnografi Komunikasi dalam Meningkatkan Interaksi Sosial Anak Berkebutuhan Khusus - Rofi’atin; Sufyanto (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study is to describe communicative events, communicative actions, communicative situations between teachers and students with autism in interacting with the school environment at SLB Aisyiah Krian. The research method used in this research is using qualitative research with an ethnographic communication study approach. The results of the study explain that the Ethnography of Communication in Improving Social Interaction of Children with Special Needs